The impact of foreign electronic games on Arabic language and culture in Saudi Arabia - Al Mgirah, Haya Ali Mohammed; Al-Basala, Aida Saeed; Al-Rumhi, Hamood Mohammed (Arts for Linguistic & Literary Studies, 2025)
This paper explores the phenomenon of electronic games from a linguistic perspective, focusing on their impact on education, culture, communication, and language acquisition and highlighting the impact of these games on language and culture in Saudi Arabia. A closed-ended questionnaire was distributed electronically to a sample of 170 participants. Statistical analysis was conducted using SPSS and Smart PLS4 programs. The results revealed that the majority of youth, regardless of gender, increasingly use electronic games in foreign languages—primarily English. Playing electronic games has reinforced the dominance of English over Arabic, leading to a gradual decline in the use of the native language. This preference is largely influenced by the perception that foreign languages, particularly English, are associated with prestige and higher social status. The prevalence of foreign-language games is further supported by their high quality and accessibility via the internet and mobile applications, in addition to peer influence. The study recommends promoting the development of innovative Arabic-language games, encouraging local game developers, dubbing foreign games into Arabic, and replacing foreign character names with culturally relevant Arabic alternatives to preserve identity and appeal to younger generations.